2008
DOI: 10.1007/s10067-008-0976-z
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular diastolic function evaluated with tissue Doppler imaging in children with familial Mediterranean fever

Abstract: The aim of this study was to assess the left ventricular diastolic function using conventional echocardiography and tissue Doppler imaging in children with familial Mediterranean fever. This study included 29 (13 males and 16 females) patients and 30 healthy subjects as controls. Body mass index was calculated and arterial blood pressure was monitored. After an overnight fast, venous blood samples were taken and serum amyloid A protein, C-reactive protein, serum-fasting glucose, total cholesterol, triglyceride… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 23 publications
0
18
2
Order By: Relevance
“…Noninvasive diagnostics of the left ventricular diastolic dysfunction in pediatric patients is still based on conventional echocardiographic Doppler parameters. The literature provides few reports on usage of TDI parameters in the assessment of left ventricular diastolic function in children with various pathologies that may lead to diastolic heart failure [1016]. …”
Section: Introductionmentioning
confidence: 99%
“…Noninvasive diagnostics of the left ventricular diastolic dysfunction in pediatric patients is still based on conventional echocardiographic Doppler parameters. The literature provides few reports on usage of TDI parameters in the assessment of left ventricular diastolic function in children with various pathologies that may lead to diastolic heart failure [1016]. …”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, cardiac function has been investigated in children with FMF by using conventional & tissue Doppler imaging [3]. Systolic function was found to be normal, while diastolic dysfunction was reported.…”
Section: Discussionmentioning
confidence: 99%
“…It is a genetic disorder inherited as an autosomal recessive disease [2] and is characterized by recurrent febrile inflammatory attacks of serosal and synovial membranes. FMF predominantly affects the populations arising from the Mediterranean basin and seen in nearly every country [3]. Its phenotype includes recurrent attacks of peritonitis, pleuritis, pericarditis, synovitis, arthritis, and fever [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 There are some studies that claim FMF is in association with diastolic dysfunction. 9,10 However, myocardial function has been investigated in FMF patients and diverse results were obtained from different studies. In a study, FMF was found to be in relation with reduced left ventricular (LV) strain in children, 11 but there is lack of research that shows the relationship between FMF and systolic function in adults.…”
mentioning
confidence: 99%